1995
DOI: 10.1111/j.1540-8159.1995.tb06734.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial Fragmented Electrogram and Prediction of Ventricular Tachycardia by Body Surface Signal‐Averaged Electrocardiographic Mapping

Abstract: Signal-averaged (SA) electrocardiography and SA electrocardiographic mapping were performed in 50 patients with old myocardial infarction, 19 of whom had left ventricular aneurysm and 11 of whom had clinical sustained ventricular tachycardia. The SA electrocardiogram and SA electrocardiographic mapping data were then compared with those obtained by endocardial catheter mapping in patients with or without fragmented electrograms, sustained ventricular tachycardia, and ventricular aneurysm. Compared to SA electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Other studies have demonstrated a strong correlation between fractionated endocardial electrograms and AF episodes 33,34 . Fragmented ventricular activation detected by endocardial electrograms has been already correlated with low-amplitude and high-frequency signals detected on body surface SAECG 35,36 . Thus, it is reasonable to conclude that the spectral turbulence of the surface P-SAECG reflects the presence of potential fragmented intracavitary atrial activation.…”
Section: (B) Mec (%) (C) Sec (%) (D) Met (Hz) (E) Set (Hz)mentioning
confidence: 99%
“…Other studies have demonstrated a strong correlation between fractionated endocardial electrograms and AF episodes 33,34 . Fragmented ventricular activation detected by endocardial electrograms has been already correlated with low-amplitude and high-frequency signals detected on body surface SAECG 35,36 . Thus, it is reasonable to conclude that the spectral turbulence of the surface P-SAECG reflects the presence of potential fragmented intracavitary atrial activation.…”
Section: (B) Mec (%) (C) Sec (%) (D) Met (Hz) (E) Set (Hz)mentioning
confidence: 99%
“…These tissues serve as a substrate for ventricular arrhythmias in 15% of cases, which increases the risk of sudden and non-sudden death by six-fold when compared to patients with a comparable ejection fraction without LVA. [11][12][13][14][15] It may also cause significant loss of stroke volume and may be responsible for the congestive heart failure, which is encountered in half of these patients. Thus LVA is associated with significant morbidity and mortality.…”
mentioning
confidence: 99%
“…The wall of the LVA consists of fibrous tissue as well as necrotic myocardium with islands of viable but ischemic myocardium. These tissues serve as a substrate for ventricular arrhythmias in 15% of cases, which increases the risk of sudden and non‐sudden death by six‐fold when compared to patients with a comparable ejection fraction without LVA 11–15 . It may also cause significant loss of stroke volume and may be responsible for the congestive heart failure, which is encountered in half of these patients.…”
mentioning
confidence: 99%